The Effect of the Use of Animated Videos on Student Learning Outcomes in Social Science Subjects in Grade III of the Madani Integrated Model State Elementary School - Jessicka Klarita Ombitaka; Herlina Herlina; Sisriawan Lapasere; Arif Firmansyah; Dyah Aini Purbarani (FKIP - Universitas Riau, 2026)
This study examined the effect of animated video media on the learning outcomes of third-grade elementary school students in the Natural and Social Sciences (IPAS) subject at SD Negeri Model Terpadu Madani. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The participants were 30 third-grade students selected through saturated sampling. Data were collected using a validated and reliable multiple-choice achievement test administered before and after the implementation of animated video-based instruction on the topic Various Landscapes in Indonesia. Data analysis included descriptive statistics, the Shapiro–Wilk normality test, and the Wilcoxon Signed-Rank Test. The results showed an improvement in students’ learning outcomes after the intervention, with a statistically significant difference between pretest and posttest scores. The findings indicate that animated video media effectively enhanced students’ understanding of the learning material. By integrating visual and auditory elements, the media increased students’ engagement, supported conceptual understanding, and encouraged active classroom participation. Therefore, animated video media can be considered an effective instructional alternative for improving elementary school students’ learning outcomes in IPAS. Future research with more rigorous experimental designs and larger sample sizes is recommended to strengthen the generalizability of these findings.